Polyimides with super‐high Tg and ultra‐low coefficient of thermal expansion from N‐substituted bibenzimidazole diamines. Issue 2 (4th December 2022) - Ke, Zhao; Wang, Mengxia; Gu, Qian; Li, Dongwu; Dai, Fengna; Chen, Haiquan; Qian, Guangtao; Li, Dandan; Li, Hui
Abstract: Polyimides (PIs) with super heat‐resistance and ultralow coefficient of thermal expansion (CTE) are required urgently to employ as plastic substrates in flexible‐display devices. To attain the target properties, we designed and synthesized a novel bibenzimidazole diamine characterized in having a N ‐phenyl group, namely 1‐phenyl‐2, 2′‐bibenzoimidazole‐5, 5′‐diamine (PhDABZ), and focused on an aromatic poly(benzimidazole imide) series derived from 1, 2, 4, 5‐benzenetetracarboxylic (PMDA). Incorporating bibenzimidazole and N ‐substituent effectively increase the interchain interaction and chance for flexible film formation, which provides the PIs with high glass‐transition temperature ( T g  > 480 °C) and dimensional stability (CTE < 10 ppm K −1 ). These data provide a feasible method to achieve higher thermal properties of PIs. Abstract :